The Influence of Communication Skills and Conflict Management Skills of School Principals on Teacher Performance in Public Elementary Schools - Nuraisyah Sitorus; Candra Wijaya; Fatkhur Rohman (STAI Miftahul Ula Nganjuk, 2025)
This study addresses the suboptimal performance of teachers, which is influenced by the leadership style of school principals and the organizational culture within educational institutions. Effective leadership is essential, as principals should act as facilitators, motivators, and role models for their subordinates, fostering a positive work environment. This research aims to examine (1) the impact of leadership style on teacher performance, (2) the effect of organizational culture on teacher performance, and (3) the combined influence of leadership style and organizational culture on teacher performance in Islamic Boarding Schools in Southeast Aceh Regency. Using an ex-post facto research design, the study involved a population of 110 teachers from three Islamic Boarding Schools: Darul Azhar, Darul Iman, and Darul Amin. Saturated sampling was applied, including all members of the population. The findings show that (1) leadership style significantly and positively affects teacher performance, with a p-value of 0.000 < 0.05, (2) organizational culture also positively and significantly influences teacher performance, with a p-value of 0.00 < 0.05, and (3) both leadership style and organizational culture together contribute significantly to teacher performance, accounting for 98.8% of the variance.